ESTIMATION OF ANESTHESIA EFFICIENCY DURING ENT ORGAN OPERATIONS - Begimov O. A.; Goyibov S. S; Daminov A. G. (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses reliable anesthesia in simultaneous operations. - one of the most important links in the treatment of surgical patients, the severity of surgical stress, methods of regional anesthesia, hypnosis component, artificial ventilation of the lungs, the main function of accompanying surgical anesthesia, almost all common anesthetics and opioids negatively affect on cognitive and psychomotor functions, Application of EA in combination with general onesthesia